2022
DOI: 10.1093/aob/mcac132
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy: its consequences and enabling role in plant diversification and evolution

Abstract: Background Most, if not all, green plant (Virdiplantae) species including angiosperms and ferns, are polyploids themselves or have ancient polyploid or whole genome duplication signatures in their genomes. Polyploids are not only restricted to our major crop species such as wheat, maize, potato and the Brassicas, but occur frequently in wild species and natural habitats. Polyploidy has thus been viewed as major driver in evolution, and its influence on genome and chromosome evolution has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 54 publications
0
38
1
Order By: Relevance
“…Suppression mechanisms that require insertion of ClvR into a gene required for gamete function may be challenging for related reasons. Finally, we note that plants often have a much greater ability to hybridize across species barriers than do animals 66,68 . Thus, drive in some plants may lead to spread in wild relatives-though sequence divergence at gRNA target sites, if the gRNAs are chosen to be target species specific, can prevent this.…”
Section: Clvr-bearing Pollen) and Sterile Females Modeling And Experi...mentioning
confidence: 86%
“…Suppression mechanisms that require insertion of ClvR into a gene required for gamete function may be challenging for related reasons. Finally, we note that plants often have a much greater ability to hybridize across species barriers than do animals 66,68 . Thus, drive in some plants may lead to spread in wild relatives-though sequence divergence at gRNA target sites, if the gRNAs are chosen to be target species specific, can prevent this.…”
Section: Clvr-bearing Pollen) and Sterile Females Modeling And Experi...mentioning
confidence: 86%
“…Taken with evidence from cytological studies and the complex morphological patterns in these clades ( Pennington and Styles, 1975 ; Appelhans et al., 2012 ; Paetzold et al., 2018 ; Appelhans et al., 2021 ; Guimarães and Forni-Martins, 2022 ), it points to a complex evolutionary history potentially involving local gene duplication, ancient hybridization (allopolyploidization) and autopolyploidization. These processes, especially ancient hybridization, may affect our ability to reconstruct the evolution of these clades as a bifurcating tree and interpret morphology ( Morales-Briones et al., 2021 ; Nauheimer et al., 2021 ; Heslop-Harrison et al., 2022 ). Therefore, investigation of the processes responsible for these signals of gene duplication will be critical for furthering our understanding of evolutionary relationships in these clades.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it must sustain extreme conditions, which include cold winter and hot and dry summer with annual temperatures commonly varying from 0 °C to 30 °C. Abiotic stressors have been recently implicated in genome size fluctuation and evolutionary trade-offs [ 69 , 70 , 71 , 72 ]. Recently it was also reported that genome size in plants can influence the stress tolerance of invasive and native plants via genomic plasticity [ 69 ].…”
Section: Discussionmentioning
confidence: 99%